Growth and biochemical composition of sprulina platensis and s. fusiformis under fifferent culture conditions - Md. Rafiqul Islam (Fakulti Agroteknologi dan Sains Makanan, 2011)
A study on the growth and biochemical composition of Spirulina platensis and S. fusiformis were carried out at KUSTEM. Spirulina platensis was obtained from the Planktology Laboratory, KUSTEM, while S. fusiformis was obtained from the Marugappa Chettair Research Center (MCRC), Chennai, India. The culture was maintained by repeated transfer to liquid Zarouk medium. The effect of physico-chemical factors: nutrients, salinity, pH, temperature, light intensity and urea concentration on the growth and biochemical constituents of the two strains were investigated.